PENGARUH MOTIVASI INVESTASI DAN PENGETAHUAN INVESTASI TERHADAP MINAT INVESTASI DI PASAR MODAL PADA MAHASISWA FE UNIYOS - Ichwan Bagus Airlangga; Utin Mardiana (Fakultas Ekonomi Universitas Yos Soedarso, 2020)
This study aims to determine: (1) Knowing the influence of investment motivation on investment interest in capital market at FE UNYOS students. (2) To know the influence of investment knowledge on investment interest in capital market at FE UNYOS students. (3) Knowing the influence of investment motivation and investment investment knowledge on investment interest in capital market at FE UNYOSstudents.The research design is quantitative. The population in this study is the Student Program Strata 1 Accounting Program, FE UNYOS and has passed the course of Portfolio Theory. The sample in this research is 100 students. Data collection in this study using questionnaire method. The test of the instrument was analyzed by using validity test and reliability test. Data analysis techniques used in this study are classical assumptions, simple linear regression analysis and multiple linear regression analysis.The results of this study indicate that: (1) Investment motivation has an effect on the interest of investing in capital market in FE UNY OSstudents, evidenced by probability value of 0.000 <0,05. (2) Investment knowledge has an effect on investment interest in capital market at FE UNYOS students proved with probability value equal to 0,000 <0,05. (3) The motivation and knowledge of investment simultaneously affect the interest of investing in the capital markets of FE UNYOS students, as evidenced by Fhitung of 227,363 and the probability of 0.000. (4) The independent variables together affect the dependent variable by the remaining 82.4% by 17.6% influenced by other variables.Keywords :Â Â Investment Knowledge; Investment Motivation; Investment Interest in Capital Market.